An investigation into the changing relationship between the gold price and South African gold mining industry returns - Jan J. Szczygielski; Zack Enslin; Elda du Toit (South African Journal of Business Management, 2018)
Background: It is accepted that the gold price impacts on the value of gold mining companies. Previous studies have shown that, in financial crises, gold is considered a `safe haven' investment in developed markets. Aim: The aim of the study is to investigate whether an investment in gold mining stocks do provide gold price-linked safe haven benefits to investors in an emerging economy. An understanding of the possible safe haven benefits of their companies' stocks and the variables that influence these benefits would be valuable to managers of gold companies when endeavouring to maximise shareholders' wealth through hedging and investment decisions. Methods: Regression analysis is applied to investigate the relationship between gold mining returns, the gold price and the rand–dollar exchange rate within a multifactor model motivated by the arbitrage pricing theory. Results: The results indicate that there is a strong, yet changing, relationship between the gold price, the rand–dollar exchange rate and gold mining returns. Conclusion: This study extends the understanding of the changing South African gold mining industry in a world that is still recovering from the global financial crisis.
Keywords: 650